THE ROLE OF NON-VERBAL COMMUNICATION IN SPOKEN LANGUAGE (Web of Discoveries: Journal of Analysis and Inventions, 2025)
Non-verbal communication plays a pivotal role in spoken language, shaping how messages are delivered and interpreted. Beyond words, body language, facial expressions, gestures, posture, eye contact, and tone of voice significantly contribute to the meaning of a conversation. This article explores the complex relationship between verbal and non-verbal cues in human interaction, highlighting the ways in which non-verbal communication enhances, complements, or even contradicts spoken language. Through the lens of psychology and linguistics, the article examines how cultural, social, and individual differences influence non-verbal communication patterns and how they impact interpersonal relationships. The integration of non-verbal cues with speech is essential for effective communication, particularly in conveying emotions, intentions, and subtle nuances that words alone cannot express.